ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI MINAT PENGGUNAAN E-WALLET LINKAJA SYARIAH PADA MASYARAKAT JABODETABEK - Muhamad Armand Gaffar (2023)
The presence of this sharia-based digital payment system is expected to contribute to the development of sharia economy and finance. The reality in the field is that there is still not much understanding of the LinkAja Syariah digital wallet. This study aims to determine the influence of the factors that influence interest in using LinkAja Syariah services in Jabodetabek, namely trust, perceived benefits, safety, and price. This study uses a quantitative approach with multiple linear regression methods. The population of this study is Jabodetabek people who use LinkAja Syariah services. The results obtained from this study are trust, perceived benefits are not significant while security and price have a significant influence on the intention to use LinkAja Syariah